2018
DOI: 10.1111/bjd.16917
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant activation of the type I interferon system may contribute to the pathogenesis of anti‐melanoma differentiation‐associated gene 5 dermatomyositis

Abstract: Our data confirm the aberrant activation of type I IFN system in anti-MDA5 DM. Overproduction of IFN-α linked with BAFF may be implicated in the development of ILD. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 40 publications
4
46
0
1
Order By: Relevance
“…Because neopterin is produced in response to IFN‐γ, the high level of neopterin in DM patients may represent an IFN response. In particular, the higher neopterin noted in the anti‐MDA5 antibody‐positive DM may correlate with an elevated IFN response signature that has been reported within this antibody group . Of interest, IFN‐γ has also been noted to play a role in life‐threatening RP‐ILD , but this may also reflect how neopterin may correlate to both RP‐ILD and mortality.…”
Section: Discussionmentioning
confidence: 84%
“…Because neopterin is produced in response to IFN‐γ, the high level of neopterin in DM patients may represent an IFN response. In particular, the higher neopterin noted in the anti‐MDA5 antibody‐positive DM may correlate with an elevated IFN response signature that has been reported within this antibody group . Of interest, IFN‐γ has also been noted to play a role in life‐threatening RP‐ILD , but this may also reflect how neopterin may correlate to both RP‐ILD and mortality.…”
Section: Discussionmentioning
confidence: 84%
“…Remarkably, a recent study revealed that these patients showed a high activity of type I IFN system. Although the mechanisms are still unclear, the study detected high levels of transcripts of IFN-associated sensors and several IFN-inducible genes were up-regulated in these patients ( 50 ).…”
Section: Interferonopathiesmentioning
confidence: 99%
“…High levels of initial serum ferritin, alveolar-arterial oxygen gradient (P[A-a]O2), and score of ground-glass opacity (GGO) involving the right middle lobe were reported to be poor prognostic factors in anti-MDA5-positive patients [52]. Increased serum IL-6, IL-8 and IL-10 levels were associated with RP-ILD in PM/DM, and high concentrations of IFN-a and soluble CD163, and the upregulation of IFN-inducible genes were reported in anti-MDA5-positive patients [53][54][55][56][57]. These findings suggest the upregulation of the type 1 IFN system via activation of monocytes, macrophages, or other immunocompetent cells in the pathophysiology of anti-MDA5positive dermatomyositis with RP-ILD, although further investigation is needed.…”
Section: Anti-mda5mentioning
confidence: 99%